Te puawaitanga o te ihi me te wehi : the politics of Maori social policy development : a thesis presented in partial fulfilment of the requirements for a Doctorate in Philosophy at Massey University - Ruwhiu, Leland Ariel (Massey University, 1999)
As an area of inquiry Maori social policy gives rise to several critical viewpoints - Social policy directed 'at, to, on or with Maori' in comparison to Maori social policy formulated, developed and implemented 'by Maori for Maori'. This thesis provides both an in-depth historical and contemporary analysis of the development of Maori social policy in contact times with Pakeha/Tauiwi. At the same time it also investigates the interrelationship between traditional and recent Maori interpretations of Maori wellbeing. Exploration into the politics of Maori social policy development coincides with and is intricately connected to, an analysis of Maori wellbeing. Maori social policy which is centred on Maori conceptual/theoretical knowledge, wisdom, and experience is examined and critiqued. A key feature of this thesis has been its introduction of several theoretical frameworks in order to make sense of Maori wellbeing. These analysis frameworks assist in identifying the key characteristics, underpinning principles and specific goals of Maori social policy. In addition, issues associated with researching Maori are explored. This includes an overview of general research principles, approaches and methodologies. Identification of key principles, approaches and methodologies underpinning Maori research is then presented. The thesis concludes with a framework for developing Maori social policy which meets the welfare needs of all Maori. It argues that Maori social policy is about Maori wellbeing, and Maori wellbeing draws strength from the past, present and future - Te Puawaitanga o te ihi me te wehi.
Keywords: Maori (New Zealand people); Government policy; Social conditions; New Zealand; Social policy; Kaupapa whakaaro; Tāngata whenua; Ora; Maori social policy; Maori well-being; Māori Doctoral Thesis